2013
DOI: 10.1002/j.0022-0337.2013.77.6.tb05530.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Virtual Reality Simulation System for Porcelain Fused to Metal Crown Preparation at Tokyo Medical and Dental University

Abstract: The use of virtual reality simulation (VRS) is a new teaching modality in dentistry, and there is scope for further research evaluating its use under different educational programs. The purpose of this study was to evaluate how VRS with or without instructor feedback inluenced students' learning and skills related to porcelain fused to metal (PFM) crown preparation. In this study, forty-three dental students in their ifth year of study at Tokyo Medical and Dental University, Tokyo, Japan, were randomly divided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
69
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(73 citation statements)
references
References 22 publications
0
69
0
Order By: Relevance
“…Similarly, a study by Yasukawa () showed that students who interacted solely with VRS for immediate feedback received a significantly lower grade on their practical exams compared with those who interacted with faculty and VRS. In contrast, Kikuchi, Ikeda, and Araki () found that when students used VRS to learn to prepare a metal ceramic crown, interactions with faculty had no effect on student performance.…”
Section: Introductionmentioning
confidence: 94%
“…Similarly, a study by Yasukawa () showed that students who interacted solely with VRS for immediate feedback received a significantly lower grade on their practical exams compared with those who interacted with faculty and VRS. In contrast, Kikuchi, Ikeda, and Araki () found that when students used VRS to learn to prepare a metal ceramic crown, interactions with faculty had no effect on student performance.…”
Section: Introductionmentioning
confidence: 94%
“…Nine studies (47.4%) took place in Europe [18][19][20][21][22][23][24][25][26], ve studies (26.3%) took place in North America [7,[27][28][29][30], three studies (15.8%) were conducted in Asia [31][32][33], one study (5.2%) was conducted in Oceania [34], and one study (5.2%) did not mention the country setting [35]. One study (5.2%) had a sample size of 9 [7], three studies (15.8%) had a sample size between 11 and 30 [22,28,34], 11 studies (57.9%) had a sample size between 31 and 50 [18-21, 23-26, 31, 33, 35], two studies (10.5%) had a sample size between 51 and 70 [29,32], and two studies (10.5%) had a sample size between 71 and 90 students [27,30]. Seven studies (36.8%) assessed second year undergraduate dental students [7,21,22,27,29,30,33], four (21%) assessed rst year [23][24][25]28], four (21%) assessed fourth year [20,32,34,35], two (10.5%) assessed third year …”
Section: Study Characteristicsmentioning
confidence: 99%
“…One study (5.2%) had a sample size of 9 [7], three studies (15.8%) had a sample size between 11 and 30 [22,28,34], 11 studies (57.9%) had a sample size between 31 and 50 [18-21, 23-26, 31, 33, 35], two studies (10.5%) had a sample size between 51 and 70 [29,32], and two studies (10.5%) had a sample size between 71 and 90 students [27,30]. Seven studies (36.8%) assessed second year undergraduate dental students [7,21,22,27,29,30,33], four (21%) assessed rst year [23][24][25]28], four (21%) assessed fourth year [20,32,34,35], two (10.5%) assessed third year [18,26], one (5.2%) assessed fth year [31], and one (5.2%) assessed a mixture of fourth and fth year [19]. Most of these studies (57.9%) assessed the student's ability in operative dentistry [18, 20-26, 29, 30, 33].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations